2016
DOI: 10.1108/nfs-10-2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponics: potential for augmenting sustainable food production in non-arable regions

Abstract: Purpose The purpose of this review of the literature is to provide readers a foundation of understanding whereby future research can move forward in the quest for global sustainable food production. Design/methodology/approach This review includes up-to-date information from evidence-based sources on hydroponics. Topics included are advantages, limitations, nutritional quality and sensory quality Findings Hydroponic growing systems offer the opportunity to at least augment traditional soil-based growing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 33 publications
2
53
0
1
Order By: Relevance
“…A critical point in assessing the advantages and disadvantages of vertical farming is the fact that hydroponic systems do not require sunlight and soil, which may have an impact on their nutritional quality. A review by Treftz et al [17] summarizes the current mixed results about nutritional comparisons between hydroponic-and soil-grown fruits and vegetables. On the one hand, studies have shown that plants or their products from conventional agriculture contain better nutrients quality [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical point in assessing the advantages and disadvantages of vertical farming is the fact that hydroponic systems do not require sunlight and soil, which may have an impact on their nutritional quality. A review by Treftz et al [17] summarizes the current mixed results about nutritional comparisons between hydroponic-and soil-grown fruits and vegetables. On the one hand, studies have shown that plants or their products from conventional agriculture contain better nutrients quality [17].…”
Section: Introductionmentioning
confidence: 99%
“…A review by Treftz et al [17] summarizes the current mixed results about nutritional comparisons between hydroponic-and soil-grown fruits and vegetables. On the one hand, studies have shown that plants or their products from conventional agriculture contain better nutrients quality [17]. On the other hand, there is research which indicate better nutrient quality for hydroponic agriculture [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Chilean northern zone has chloride levels above 200 mg/L and boron levels over 2 mg/L within the reclaimed wastewater [82]. These chloride and boron levels produce adverse effects, such as dehydration and plant wilt, within most crops [84]. However, this strategy requires public policies, which in the short term of this review can be used as a preliminary discussion tool in the country.…”
Section: Zonementioning
confidence: 99%
“…Hydroponics is a soil-free cropping system, where the belowground plant part (root) is in contact with nutrients, water, and an inert medium (this part is optional) [85]. Aeroponics is a soil-free cropping system where the belowground plant part is placed in air and adheres to an inert medium below a dark controlled environment saturated with moisture and nutrients [84]. Vegetables such as lettuce, tomatoes, cucumbers, zucchini, carrots, and ornamental species such as chrysanthemum and poinsettia have been grown below soil-free cropping systems [84,86].…”
Section: Zonementioning
confidence: 99%
See 1 more Smart Citation